The Competence of Student Teachers in Questioning Assessment through Teacher Talk in a Peer Teaching - Dwi Sulistyorini; Rachmat Ari Wibowo; Yusi Rahmawati (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2025)
This research seeks to identify the types of questions utilized by the student teachers and to analyze students' responses to the teacher's questions, both intended and unintended, across the four modes proposed by Walsh (2011). The study population consisted of five students from the sixth semester English Department at Ivet University in a peer-teaching environment. This research employed a case study design that emphasized descriptive analysis. The information was gathered through voice recordings and subsequently transcribed into text. This study demonstrated that the student teachers utilized both forms of questions across four distinct modes. The majority of them generated questions in material mode, then in managerial mode, followed by skill and system mode, with classroom context mode being last. The research findings indicated that students' responses to teachers' questions were deliberate. The majority of students respond to the questions using complete sentences. This is due to the peer-teaching setting, in which participants were not actual students but peers, since it was a peer teaching setting where the student teacher motivates them to respond in full sentences. Given that they are in their sixth semester, their speaking skills are strong.